CD28 and CD57 define four populations with distinct phenotypic properties within human CD8+ T cells. Issue 3 (4th December 2019) - Pangrazzi, Luca; Reidla, Jürgen; Carmona Arana, José Antonio; Naismith, Erin; Miggitsch, Carina; Meryk, Andreas; Keller, Michael; Krause, Adelheid Alma Nora; Melzer, Franz Leonard; Trieb, Klemens; Schirmer, Michael; Grubeck‐Loebenstein, Beatrix; et al.
Abstract: After repeated antigen exposure, both memory and terminally differentiated cells can be generated within CD8 + T cells. Although, during their differentiation, activated CD8 + T cells may first lose CD28, and CD28 − cells may eventually express CD57 as a subsequent step, a population of CD28 + CD57 + (DP) CD8 + T cells can be identified in the peripheral blood. How this population is distinct from CD28 − CD57 − (DN) CD8 + T cells, and from the better characterized non‐activated/early‐activated CD28 + CD57 − and senescent‐like CD28 − CD57 + CD8 + T cell subsets is currently unknown. Here, RNA expression of the four CD8 + T cell subsets isolated from human PBMCs was analyzed using microarrays. DN cells were more similar to "early" highly differentiated cells, with decreased TNF and IFN‐γ production, impaired DNA damage response and apoptosis. Conversely, increased apoptosis and expression of cytokines, co‐inhibitory, and chemokine receptors were found in DP cells. Higher levels of DP CD8 + T cells were observed 7 days after Hepatitis B vaccination, and decreased levels of DP cells were found in rheumatoid arthritis patients. More DP and DN CD8 + T cells were present in the bone marrow, in comparison with PBMCs. In summary, our results indicate that DP and DN cells are distinct CD8 + T cell subsets displaying defined properties. Abstract : Through microarray analysis and functional assays, we investigated the phenotype of CD28+CD57‐, CD28+CD57+, CD28‐CD57‐ and CD28‐CD57+ CD8+ T cells in humans. Our study provides new insights into T cell differentiation and senescence. Furthermore, our work suggests the importance of CD28+CD57+ CD8+ T cells in the context of vaccination and diseases.